Study of incidence of allergic conjunctivitis in patients with allergic rhinitis - Gupta, Sucheta; Gupta, Vinod (International Journal of Research in Medical Sciences, 2021)
Background: Allergic conjunctivitis (AC) accounts for 15% of eye related consultations in primary care centers. AC is commonly manifesting as itchy or watering or red eye, comprising the symptoms of the total ocular symptom scores (TOSS). Recognition of AC is unreported even in patients with recognized AR (allergic rhinitis). Therefore, the objective of the present study was to identify the incidence of AC in patients with AR. Methods: This randomized observational study was conducted on 110 patients for a 6 month period from February to July 2019, having diagnosed AR and attending the outpatient clinic in CHC Chenani, district Udhampur, Jammu and Kashmir. The patients were directly questioned if they had AC, clarified by using standard screening questions of red, itchy and watery eyes and quantified by TOSS and were asked about indirect symptoms that may be attributable to AC. Results: Among the 110 patients, 50.9% of patients identified AC on direct questioning; additional symptoms were squint at 47.3% and blinking at 51.2%. Olopatadine, significantly reduced TOSS scores within 5 minutes of treatment and 80.9% showed improvement, which identified 39% silent sufferers of AC. A total of 90% AC subjects were identified through TOSS symptoms and totally 95.5%, detecting additional symptoms. The other co-morbidity that was associated with allergic conjunctivitis was allergic dermatitis. Conclusions: The screening questions could identify only about 56% of the patients with AC. Additional specific questioning and a therapeutic challenge in suspected patients can help identify patients who may benefit from treatment of AC.